(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to test the relationship between customer relationship management and its impact on tourism development, as well as to identify the nature of the practice and interest of the Antiquities and Heritage Authority and its affiliated sites, as the importance of the study stems from the limitations of previous studies that tried to identify and know the type of relationship between research variables (Customer Relationship Management) Tourism development), add to this the researcher’s attempt to address a realistic problem that mainly affects the tasks and work of the Antiquities and Heritage Authority at the near and distant level, so the study adopted the intentional stratified sampling method, and distributed (100) questionnaires as a main tool for data collection, to (the director, assistant director, Section head, division official, employee) at the authority’s headquarters, so the number of recovered persons was (86), of which (79) were a valid questionnaire for statistical analysis. For this purpose, the researcher employed two statistical packages (SPSS V.26, SMART PLS V. 3.3.8), and support The study uses a descriptive, analytical, exploratory, and historical approach, and used statistical methods to analyze the practical side (weighted arithmetic mean, standard deviation, coefficient of variation, relative importance, T-test, Pearson’s simple correlation coefficient, and the curvature. Dar Al Khatti Al Simple and Multiple), and the descriptive and inferential statistical analysis concluded the most prominent result of employing the Antiquities and Heritage Authority to manage customer relations in tourism development, especially when it uses the focus on the main customers and organizational efficiency in promoting the tourism development of the Authority.